Breaking the cycle : can glyphosate and willow cuttings disrupt positive feedbacks that sustain reed canarygrass (phalaris arundinacea) monocultures? - Merriman, Michael Paul (My University, 2014)
Restoring invaded ecosystems requires the reduction of any positive feedbacks created by the invader. Feedbacks created by reed canarygrass (Phalaris arundinacea) in theUpper Mississippi River floodplain include early season growth, a thick canopy and an extensive belowground rhizome system. We tested a novel restoration strategy designed to reduce these feedbacks by applying broad spectrum herbicide (glyphosate) in late fall 2012 and 2013, and by planting willows as a native competitor. We conducted the experiment in a site dominated by reed canarygrass in the Upper Mississippi River (UMR) floodplain south of La Crosse, WI over two growing seasons. In the first year of the experiment, glyphosate reduced reed canarygrass percent cover early in the growing season. At the end of the second year, glyphosate reduced reed canarygrass belowground biomass. Willow stakes that were planted in fall resulted in poor establishment. Stakes that were planted in spring exhibited higher height and canopy spread in glyphosate- treated plots. Ground-level light availability was higher in plots that had surviving willows than in plots without willows. Thus, results demonstrate the potential for willow stakes to establish in dense reed canarygrass, but additional information on how to maximize the success of the approach is still needed.
Keywords: Hardwoods -- Wisconsin.; Reed canary grass -- Wisconsin.; Glyphosate -- Environmental aspects -- United States.